Serum Lipid Profile and Electrocardiographic Changes in Young Smokers - Uday B. Nayak; Jinzy Mariam George; Pradeep T.V; Naveen Naveen (International Journal of Public Health Science (IJPHS), 2013)
Smoking represents an important and rapidly growing global cause of cardiovascular mortality and morbidity.Cigarrette smoking is one of the major modifiable risk factors of cardiovascular disease, unless smokers are able to quit,  approximately 40% of them will die prematurely.The need of the hour is timely intervention through smoking cessation.Our study was carried out in young smokers to demonstrate the effects of smoking on lipid profile and electrocardiographic changes. We aimed to study the effect of smoking on lipid profile and electrocardiographic changes in young smokers.The study design was a cross sectional study comprising 75 male smokers and 75 healthy controls.Smoking history and physical examination was done .Fasting sample was analysed for lipid profile and electrocardiograph of all subjects were recorded.The statistical anaylsis between mean values were evaluated by student‘t’ test. Statistical significance was assessed by chi-square test, p<0.001 was considered to be significant.The mean pulse rate,  the mean systolic blood pressure,  abnormal lipid profile and prolonged Qt interval were significantly higher in smokers (p<0.001).We demonstrated significant lipid abnormalities and electrocardiographic changes in young smokers who form an important risk group and target population in whom smoking cessation counseling should be carried out to decrease long term cardiovascular risk.DOI: http://dx.doi.org/10.11591/ijphs.v2i1.1679